Steinbeck at Freshman/Sophomore event at Stanford - George Mors:::Creator::::::::::::
A line of young men with their arms linked. Steinbeck stands front and center, shirtless and in suspenders. RESTRICTED USE. This image digital only, the hard copy is close-up of Steinbeck.